VAGINAL AND ORAL MISOPROSTOL FOLLOWING MIFEPRISTONE ADMINISTRATION IN MEDICAL TERMINATION OF PREGNANCY UP TO 49 DAYS: A COMPARATIVE STUDY - VARDAINI, DIVYA (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The objective of this study was to compare and evaluate the efficacy, safety, adverse effects, and patient compliance of vaginal versus oral misoprostol in medical termination of pregnancy after tablet misoprostol up to 49 days of gestation. Methods: A comparative study of 100 patients divided randomly assigned to two control groups. Results: The study showed that 200 mg mifepristone followed by 800 mcg vaginal misoprostol is more effective for medical termination in gestational age up to 49 days as compared to 200 mg mifepristone followed by 400 mcg oral misoprostol. Conclusion: While both routes of administration are safe, gastrointestinal side effects are more with oral misoprostol. The vaginal route is more acceptable to the patients enrolled in the study.